2010
DOI: 10.1037/a0019715
|View full text |Cite
|
Sign up to set email alerts
|

When risk seeking becomes a motivational necessity.

Abstract: Four studies demonstrate the importance of self-regulatory mechanisms for understanding risk-seeking behavior under loss. Findings suggest that risk seeking becomes a motivational necessity under 3 conditions: (a) when an individual is in a state of loss; (b) when the individual is in a prevention-focused regulatory state (E. T. Higgins, 1997); and (c) when the risky option alone offers the possibility of eliminating loss. In situations involving loss, prevention motivation but not promotion motivation (whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
183
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 230 publications
(207 citation statements)
references
References 109 publications
(169 reference statements)
18
183
6
Order By: Relevance
“…This provides direct evidence that the risky behaviors under all DOSPERT domains were perceived to involve significant potential for loss. And replicating earlier work (Scholer et al, 2010), neither promotion or prevention motivation was associated with perceived risk.…”
Section: Perceived Risk Losses and Gainssupporting
confidence: 59%
See 4 more Smart Citations
“…This provides direct evidence that the risky behaviors under all DOSPERT domains were perceived to involve significant potential for loss. And replicating earlier work (Scholer et al, 2010), neither promotion or prevention motivation was associated with perceived risk.…”
Section: Perceived Risk Losses and Gainssupporting
confidence: 59%
“…Recent study has further confirmed that prevention-focused individuals become risk-seeking in the financial domain only (a) when they experience themselves in a clear state of loss and (b) risk-seeking is the only way to return to the status-quo ante (Scholer et al, 2010). Prevention-focused individuals are not risk seeking when they are in a state of non-loss or as a way to increase gains (Zou et al, 2014).…”
Section: Prevention Motivationmentioning
confidence: 84%
See 3 more Smart Citations